First, multiply the two terms in parenthesis. To multiply these two terms you multiply each individual term in the left parenthesis by each individual term in the right parenthesis.
y = (color(red)(x) + color(red)(4))(color(blue)(2x) - color(blue)(3)) - 3x^2 + 6xy=(x+4)(2x−3)−3x2+6x becomes:
y = (color(red)(x) xx color(blue)(2x)) - (color(red)(x) xx color(blue)(3)) + (color(red)(4) xx color(blue)(2x)) - (color(red)(4) xx color(blue)(3)) - 3x^2 + 6xy=(x×2x)−(x×3)+(4×2x)−(4×3)−3x2+6x
y = 2x^2 - 3x + 8x - 12 - 3x^2 + 6xy=2x2−3x+8x−12−3x2+6x
We can now group and combine like terms:
y = 2x^2 - 3x^2 - 3x + 8x + 6x - 12y=2x2−3x2−3x+8x+6x−12
y = (2 - 3)x^2 + (-3 + 8 + 6)x - 12y=(2−3)x2+(−3+8+6)x−12
y = -1x^2 + 11x - 12y=−1x2+11x−12
y = -x^2 + 11x - 12y=−x2+11x−12